Report of 22nd ASEAN Inter-parliamentary organization general assembly - Asean inter- parliamentary assembly, Hội đồng liên nghị viện ASEAN (ASEAN Inter - Parliamentary Assembly (AIPA), 2001)
Hội nghị lần thứ 22 của Tổ chức liên nghị viện ASEAN được tổ chức tại Băng Cốc, Thái Lan từ ngày 2-7 tháng 9 năm 2001.